Erratum to: Computational study of Th4+ and Np4+ hydration and hydrolysis of Th4+ from first principles (Journal of Molecular Modeling, (2017), 23, 3, (69), 10.1007/s00894-017-3252-9) - Amador, Davi H. T.; Sambrano, Julio R. [UNESP]; Gargano, Ricardo; de Macedo, Luiz Guilherme M. (Springer Nature, 2017)
As originally published, the article contained a few minor errors. In order to avoid any confusion or misunderstanding, we would like to make the following corrections: 1) The correct temperature for entropy calculations was 298.15 k and not 198.15 K; the correct grid quadrature employed for the numerical XC term was m3 and not m5. 2) The last line in abstract should be: “Finally, this methodology has the advantage…” instead of “Finally, our methodology has the advantage…”. 3) On page 69-4, before the equations (7) and (8) should be: “The values were calculated according the equations [44],” instead of “The values were calculated according the equations,”. 4) On page 69-4, after equations (7) and (8) should be: “We had to approximate ΔHH 0 by ΔEH since An(g) 4+H0 data were not available, as done by Wiebke et al [44].”. 5) On page 69-4, The ΔG Solv0 instead of “ΔG 0 Solv”. 6) On page 69-2, should be: “…the recommended values [47,48] of 172 and 130 pm were used.” instead of “the recommended values [47, 48] of r of 172 and…”. These corrections do not affect any results or conclusions of the published work.